Considerations for making informed choices about engaging in open qualitative research. Issue 5 (3rd September 2021) - Tamminen, Katherine A.; Bundon, A.; Smith, B.; McDonough, M. H.; Poucher, Z. A.; Atkinson, M.
ABSTRACT: There is currently little guidance that exists for researchers in the sport and exercise sciences on open qualitative research practices. The purpose of paper is to provide researchers with guidance regarding the considerations necessary for making informed decisions about engaging in open research practices within qualitative inquiry. The guidance was developed through a series of four working group meetings with experts in qualitative research and meetings with key stakeholders (study participants, journal editors, and data management experts). The wider open qualitative research literature also informed the guidance. Nine core values were first identified as underpinning the considerations for engaging in open qualitative research practices: Choice (academic freedom and participant autonomy); Plurality not replication; Flexibility and emergent design; Transparency; Relational ethics; Quality; Education; Equity; and Responsibility. Considerations for researchers are then provided in the following areas as they pertain to open science practices in qualitative inquiry: Types of Data; Types of Studies; Participant Groups; Anonymity and Confidentiality; Participant Consent; Storage and Stewardship of Qualitative Data; Knowledge Dissemination and Open Access Publications; Cost, Time, and Resources; and Preregistration of Qualitative Studies. This paper provides an initial framework for identifying considerations for engaging in open qualitative research practices. These considerations will help qualitative researchers make informed decisions about and plan for implementation of open science practices, as well as assessing the risks and benefits of open science practices in qualitative inquiry.